Poster Presentation as A Tool to Assess Students’ Academic Speaking Performance: Teachers and Students’ Perspectives - Renny Tarigan; Listyani Listyani (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2021)
A poster presentation is a way that is done to share or inform a research data and information in oral communication. Through poster presentation, the presenters will be able to present the data easily. In education, poster presentation is always used for the research seminar and the conference. For the English-speaking students, they use a poster presentation as a project to learn English and how they can use English as the academic speaker. This is the reason why the Academic Speaking classes at an English Language Education Program (ELEP), in a private university in Central Java, Indonesia used the poster presentation as the final project to assess students’ performance. The study was conducted at the Faculty of Language and Arts, at a private university in Central Java, Indonesia. The aim of the study is to see how the teachers and students’ perceptions about the use of poster presentation and how it can increase the students’ academic speaking performance. The research participants were two of Academic Speaking class' lecturers and two students of batch 2016. They were interviewed using an audio recording and also the interview protocol. Based on the interview, there are some different opinions about the use of poster presentation in Academic Speaking class. Overall, the results found that the use of poster presentation, which is a form of speaking skill assessment, could increase the students’ academic speaking performance such as eye contact, gesture, fluency, pronunciation, vocabulary, and knowledge.